Thriving at work: Impact of psychological capital and supervisor support - Paterson, Ted A.; Luthans, Fred; Jeung, Wonho (Journal of organizational behavior, 2014)
Thriving at work is a positive psychological state characterized jointly by learning and vitality. Conventional wisdom and some initial research indicate that such thriving benefits both employees themselves and their organizations. This study specifically tests thriving at work by linking it to a theoretically important personal outcome variable (self-development), refining its relationship with agentic work behaviors (task focus and heedful relating), and proposing and testing two new antecedent variables (psychological capital and supervisor support climate). Using structural equation modeling on a sample of 198 dyads (employees and their supervisors), strong support was found for the theory-driven hypothesized relationships. The results contribute to a better understanding of positive organizational scholarship and behavior in general and specifically to the recently emerging positive construct of employees’ thriving at work.